2002
DOI: 10.5194/angeo-20-461-2002
|View full text |Cite
|
Sign up to set email alerts
|

He<sup>+</sup> dominance in the plasmasphere during geomagnetically disturbed periods: 1. Observational results

Abstract: Abstract.Observations made by the DMSP F10 satellite during the recovery phase from geomagnetic disturbances in June 1991 show regions of He + dominance around 830 km altitude at 09:00 MLT. These regions are co-located with a trough in ionisation observed around 55 • in the winter hemisphere. Plasma temperature and concentration observations made during the severe geomagnetic storm of 24 March 1991 are used as a case study to determine the effects of geomagnetic disturbances along the orbit of the F10 satellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Comparisons of the H + and He + plasmaspheres are of interest because the extreme ultraviolet (EUV) imager on board the IMAGE satellite shows the He + plasmasphere and its structure, which is generally assumed to correspond to that of the higher density H + plasmasphere. However, observations show that He + densities can exceed H + densities during early-stage refilling (Horwitz et al, 1990a;Denton et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of the H + and He + plasmaspheres are of interest because the extreme ultraviolet (EUV) imager on board the IMAGE satellite shows the He + plasmasphere and its structure, which is generally assumed to correspond to that of the higher density H + plasmasphere. However, observations show that He + densities can exceed H + densities during early-stage refilling (Horwitz et al, 1990a;Denton et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This diurnal variation is largely absent from the H + curves. To obtain a comparison between these simulations and the results of Denton et al (2002), who found He + /H + density ratios exceeding unity in the winter-hemisphere topside ionosphere during refilling, we plotted (not shown) H + and He + concentrations at an altitude of 900 km, 11-50 h after the storm for the run shown in Figs. 3 and 4.…”
Section: H + and He + Concentrationsmentioning
confidence: 99%
“…Strong Injection CRRES dawn-dusk electric field vs. Dst and L when -10 < dDst/dt < -1 nT/hr Average CRRES dawn-dusk electric field as a function of L and of Dst; panels show the L-dependence as a function of dDst/dt for (a) weak injection (À10 < dDst/dt < À1 nT/hr); (b) strong injection (dDst/dt < À10 nT/h); (c) weak decay (+1 < dDst/dt < + 10 nT/h) and (d) strong decay (dDst/ dt > + 10 nT/h) (Rowland and Wygant, Personal Communication 2005; see also Rowland and Wygant, 1998). refill more quickly than other species (e.g., Denton et al, 2002). Indeed, measurements from the DE1 RIMS instrument show that the He + population can vary between $2% and 50% of that of H + by number (Horwitz et al, 1984;Moldwin, 1997).…”
Section: Weak Injectionmentioning
confidence: 97%
“…Denton et al, 2002). However, the micro-physics responsible for the progression of the refilling process is poorly understood.…”
Section: Plumementioning
confidence: 98%
“…It has been noted that the topside ionosphere is a sensitive indicator of the composition and dynamics of the thermosphere. Most recently, layers of He + at middle latitudes have been investigated by Gonzalez and Sulzer [1996] and Denton et al [2002]. Seasonal and solar cycle variations in the ion composition have been investigated by West and Heelis [1996], and the relationships between ion temperature and composition have been investigated by Venkatraman and Heelis [1999].…”
Section: Introductionmentioning
confidence: 99%